PENGARUH PERSENTASE NAUNGAN DAN PUPUK BOKASHI KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Antar Sofyan; Nikmah Nikmah; Tuti Heiriyani (Universitas Lambung Mangkurat, 2022)
Tomato is a plant that has high economic value in Indonesia. Tomato fruit productivity is decreasing every year, one of the factors that affect tomato production is environmental conditions that do not support plant growth. Providing shade can avoid excess rainwater that can affect the growth process. This study aims to determine the effect of shade percentage, dose of bokashi fertilizer, and the interaction between percentage of shade and dose of bokashi fertilizer on growth and yield of tomato plants. This study used a factorial Randomized Block Design (RAK), the first factor was shade (N), namely 0% paranet (N0), 40% paranet (N1) and 60% paranet (N2) and the second factor was chicken manure bokashi fertilizer. (B) namely 0 tons/ha (B0), 35 tons/ha (B1), 45 tons/ha (B2), 55 tons/ha (B3), and 65 tons/ha (B4), with 15 treatments and 2 treatments. replications obtained 30 test units. The results showed that the percentage of shade had no significant effect on plant height, number of leaves, number of flowers, and fruit weight, the best dose of chicken manure bokashi in N1B4 treatment was 40% and shade 65 tons/ha, and there was no interaction between shade and fertilizer. bokashi on growth and yield.